Pengembangan Sistem Informasi Terintegrasi pada Toko Dynamica Music Berbasis Web - Kelvin Meiiko; Mira Ziveria (UNIVERSITAS KALBIS, 2022)
Dynamica Music Store is a shop that operates in the field of sound systems that sell a variety of sound system equipment, which already has a previous system. However, the current system only handles buying and selling activities, for other activities it is still conventional. This causes a lot of time to process existing transactions and the level of human error is quite high. The purpose of this research is to develop an integrated information system in the Dynamica Music store that can handle all the activities that exist in the integrated Dynamica Music store. The system development method in this research uses System Development Live Cycle (SDLC) with prototyping method and system modeling using Unified Modeling Language (UML) and PHP programming language. Testing this system uses alpha testing with the Black Box method. The results of this study are in the form of an integrated information system on the web-based Dynamica Music store. Based on the results of testing and evaluation, the system is suitable with the user needs and can be used at the Dynamica Music store.